Psychological Support for Young Adults with Down Syndrome: Dohsa-Hou Program for Maladaptive Behaviors and Internalizing Problems - Fujino, Haruo (Frontiers in Psychology, 2017)
Psychological and psychiatric dysfunction is a major problem in a substantial proportion of young adults with Down syndrome. Some patients develop psychiatric issues, such as depressive, obsessive-compulsive, or psychotic-like disorders, in their late adolescence or young adulthood. Furthermore, these individuals may experience moderate to severe emotional and psychological distress. Development of a psychosocial treatment to address these issues is needed in addition to psychotropic medication. The current study reports two cases of young adults with Down syndrome, who presented psychiatric symptoms and marked disruption in their daily lives. These individuals participated in a Dohsa-hou treatment program. Following treatment, adaptive levels, maladaptive behaviors, and internalizing problems were evaluated by the Vineland Adaptive Behavior Scales-II. Participants showed improvement in maladaptive behaviors and internalizing problems; however, improvement in these areas may be influenced by baseline severity of the problems. This case report suggests that Dohsa-hou could be an effective therapeutic approach for maladaptive and internalizing problems in adults with Down syndrome.